Using Newman Error Analysis to Detect Students’ Error in Solving Junior High School Mathematics Problem - Ahzan, Zulkaidah Nur; Simarmata, Justin Eduardo; Mone, Ferdinandus (Jurnal Pendidikan MIPA, 2022)
The existence of student errors is due to the inability of the students to receive and process the information contained in the given questions. Therefore, it is necessary to conduct an analysis to find out student errors so that the results obtained in the analysis can be used by teachers to provide appropriate assistance to students, either through methods or media in learning mathematics. This study is a qualitative descriptive study. The purpose of this study was to find out how many errors were made by the eighth-grade class of Nurul Falah MTs in solving math problems according to Newman’s theory in school year 2021/2022. So that solutions to reduce errors can be found and also to emphasize which parts require a deeper understanding in solving math problems. The results of the analysis showed that the percentage of student errors in the Reading Error (RE) phase was 13.33%, Reading Comprehension (RC) phase was 42.22%, Transformation Error (TE) phase was 28.89%, Process Skill (PS) phase was 71.11%, and the Encoding Error (EE) phase was 86.67%. From the results of the analysis, it can be seen that the most errors made by students are Encoding Error, which are 86.67%. Keywords: student error analysis, Islamic junior high school, Newman’s Theory. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp459-473